Autonomy, Degrowth and Prefigurative Politics: Voices of Solidarity Economy Activists amid Economic Crisis in Greece - Yiannis Zaimakis (Coordinamento SIBA, 2018)
Drawing upon in-depth interviews with key informants of grassroots alternative organisations in anti-austerity Greece, the study sheds light on the structures of meanings of invisible voices, revealing the motives, worldviews and value-systems that lay behind their actions. Using critical discourse analysis, the text offers a thorough understanding of the meaning and experience of building social and economic experiments with transformative potential within the solidarity economy alternative, in the context of the Greek economic crisis. The narratives of solidarity economy informants reveal militant investigations, ro-mantic humanism, egalitarian goals and an ethos of collectivism that call into question the prevalent capi-talist imaginary. Participants employ utopian thinking, imagining a future that departs significantly from what we know. They call on us to re-assess hegemonic values and norms in the light of alternative realities which embody forms of workers' cooperativism, participatory actions and ways of being, which prefigure the future vision of another form of social life.